Type III collagen disorders: A case report and review of literature - A Anitha; Mahesha Vankalakunti; Vishwanath Siddini; Kishore Babu; Ravishankar Bonu; Sudarshan Ballal (Wolters Kluwer Medknow Publications, 2016)
Collagen type III is a normal component of interstitium and blood vessels. Collagenofibrotic glomerulopathy (CG) and nail patella syndrome (NPS) are the diseases of abnormal type III collagen deposition. In spite of these curved frayed structures with a periodicity of 45-60 nm are deposited in subendothelium and mesangium in CG, they are found only in the basement membrane in NPS. The clinical features of CG are confined to the kidney, NPS has associated extra-renal manifestations. Electron microscopy is essential to make the renal diagnosis in both these rare diseases. Both the entities considered to be systemic diseases evidence to suggest similar deposition in other organs, understanding etiopathogenesis and disease progression await research.